Programa computacional alerta de deslizamentos João Pessoa/PB - Silva, Abimael Isaque Landim da (2021)
Mass movement is the geodynamic process that most affects Brazil. The excess of rainfall is the main agent that generates such movements. Furthermore, the growth, the urbanization of the cities and the subsequent use and occupation of risk areas through the human interference are responsible for the decrease of the land stability in slopes and hillsides. Many studies have already been developed to verify the relationship between landslides and rainfall. Through these studies, it was possible to create curves that correlate the mass movements and rainfall, and they allow the verification for which limit values for daily rainfall and for accumulated rainfall the mass movements are started. In this manner, it is necessary to monitor the levels of precipitation that start the mass movements and to warn the population of these risks. Therefore, the software “Programa Alerta de Deslizamentos João Pessoa/PB” was elaborated to help the actions taken by the Civil Defense of João Pessoa, through an automatic monitoring system and risk warning. The software was developed in Excel®, using the Visual Basic for Applications (VBA) programming language, and in Power BI®, which produces dynamic reports with the compilation of the alert data that was sent and with the landslides registered by the Civil Defense. Initially, studies regarding the theory of correlation between rainfall and landslides were carried out. Then, all the codes and the interface of the software were developed, followed by repeated tests to judge if the obtained results were satisfactory, as well as the training of the interns and finally, the implantation of the software in the Civil Defense of João Pessoa.